Deformation dynamics of a neutron-irradiated aluminum alloy: An in situ synchrotron tomography study. (15th January 2023) - Chai, H.W.; Fan, D.; Yuan, J.C.; Hu, L.; Xie, H.L.; Du, G.H.; Feng, Q.J.; Zhou, W.; Huang, J.Y.
Graphical abstract: Abstract: To reveal the effects of long-term neutron irradiation on the mechanical behavior of nuclear materials, in situ quasi-static uniaxial tensile tests are conducted on an LT21 aluminum (Al) alloy from a decommissioned research reactor. Scanning/Transmission electron microscopy (SEM/TEM), and micro CT are first applied to characterize the microstructures of LT21 Al alloys aged naturally and neutron-irradiated for 30 years. In situ synchrotron micro computed tomography (CT) is adopted to characterize the deformation and damage dynamics of this LT21 Al. A new particle tracking analysis technique is proposed to quantify the displacement/strain fields and microstructural evolution (e.g., particle movement and pore growth) in the irradiated sample. Long-term irradiation induces considerable microstructural changes in the LT21 Al alloy, including the precipitation/aggregation of micron-sized Si particles and nanoscale Mg 2 Si particles. In addition, the size of pores and particles in the irradiated material appear considerably larger than that in the unirradiated material. During tension, the alloy undergoes elastic-plastic deformation followed by shear-dominated necking failure. The porosity and pore size exhibits an overall increase with increasing loading. Formation of new pores occurs in two modes, formation at the particle-matrix interfaces and random formation across the sample. For mode one, pores tend to nucleate at the top and bottom ends of a particle (relative to the loading direction). Formation of new pores and growth of initial and newly-nucleated pores occur simultaneously and contributes approximately equally to damage accumulation in the irradiated LT21 Al alloy before necking occurs. The deformation dynamics deepens our understanding of the aging of nuclear materials.